Influence of institutional pressure on megaproject social responsibility behavior - Xie, Linlin; Xu, Ting; Han, Ting; Xia, Bo; Chen, Qing; Skitmore, Martin (Journal of Civil Engineering and Management, 2022)
To explore the law of megaproject social responsibility behavior (MSRB) among internal organizations under institutional pressure, this paper presents a theoretical and empirical study to investigate how institutional pressure affects MSRB through the mediating role of organizational social responsibility cognition and the mediating roles of the communication mechanism and relationship strength based on new institutional sociology. Based on a total of 147 responses from a broad questionnaire survey, structural equation modelling (SEM) was used to test the proposed hypotheses. The research results show that institutional pressure has a promoting effect on MSRB, and organizational social responsibility cognition mediates the relationship between institutional pressure and MSRB. Additionally, the communication mechanism and relationship strength have no effect on the relationship between institutional pressures and MSRB. The research results provide a new theoretical foundation for the analysis of MSRB and practical suggestions for policymakers on the governance of MSRB.